Effect of Stirring Time on Sodium Silicate Synthesis From Mount Kelud Volcanic Ash - Isna Nurhidayati; Endang Tri Wahyuni; Nurul Hidayat Aprilita; Sarwendah Ratnawati Hermanto (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2021)
This study performed the synthesis of sodium silicate from the volcanic ash of Mount Kelud with various stirring time in the sodium silicate synthesis process. Synthesis of sodium silicate was carried out using alkaline extraction at low temperature. This method is based on the solubility of silica under alkaline conditions and is proven to be more effective than the smelting method. The dissolution of silica contained in the volcanic ash of Mount Kelud was carried out using NaOH solution to form a Na2SiO3 solution. This process also studied the effect of stirring time on the amount of dissolved silica, with the stirring time of 0.5; 1; 1.5; 2; 2.5; 3 and 4 hours. The dissolved silica levels were tested using AAS. The amount of dissolved silica increased sharply with the longer length of stirring time, however for a stirring time of more than 2.5 hours, the dissolution was slow. The study revealed that the optimal result time was obtained from the stirring time of 2.5 hours with dissolved silica content of 19.82%. Keywords: volcanic ash, silica, sodium silicate, stirring time